Implementasi Teori Psikodinamika dalam Mengatasi Kesehatan Mental - Zahra Hamidah; Khalish Istiqomah; Nayla Debi Haliza; Ati Kusmawati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Mental health issues are gaining increasing attention across various sectors of society. One approach used to understand and address these problems is psychodynamic theory, which emphasizes unconscious conflicts and past experiences. This study aims to explore how the application of psychodynamic theory can aid in the healing process of mental health disorders, particularly among individuals with childhood trauma and anxiety disorders. A qualitative method was employed, using a case study approach involving three participants who underwent psychodynamic therapy for six months. The results indicate that through this therapy, participants were able to identify the deep-rooted sources of emotional conflict and demonstrated significant improvement in emotional regulation and interpersonal relationships. These findings highlight the importance of understanding unconscious dynamics in psychological interventions. This research recommends the integration of psychodynamic theory into modern psychotherapy practices as an alternative approach to addressing mental health issues.